2018
DOI: 10.1155/2018/7245956
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Poplar Buds on Hyperglycemia, Dyslipidemia, Oxidative Stress, and Inflammation in Streptozotocin-Induced Type-2 Diabetes

Abstract: The effects of propolis on blood glucose regulation and the alleviation of various complications caused by diabetes have been widely studied. The main source of propolis in the northern temperate zone is poplar buds. However, there is limited research on the antidiabetic activity of poplar buds. In order to evaluate the effect of poplar buds on type-2 diabetes, crude extract and 50% fraction of poplar buds were used to feed streptozotocin-induced type-2 diabetic mice. The results showed that 50% fraction could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
2
21
0
1
Order By: Relevance
“…It is well known that diabetes can cause different types of inflammation. In this study was also shown that this extract could reduce inflammatory factors, such as IL-6, TNF-α, MCP-1 and COX-2 in liver homogenate [65].…”
Section: Antidiabetic Propertiessupporting
confidence: 64%
“…It is well known that diabetes can cause different types of inflammation. In this study was also shown that this extract could reduce inflammatory factors, such as IL-6, TNF-α, MCP-1 and COX-2 in liver homogenate [65].…”
Section: Antidiabetic Propertiessupporting
confidence: 64%
“…On the other hand, glycated albumin can be used to assess blood glucose level for a shorter period since its half-life is less than three weeks [197]. For animal models, Hb1Ac is often used to assess diabetic states [129,130,131,154,157].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Thus, the antioxidation abilities of tissues can be tested to elucidate intrinsic anti-diabetes properties. For this purpose, amounts of antioxidant enzymes such as GPx, CAT, superoxide dismutase (SOD), glutathione S-transferase (GST), and antioxidant glutathione (GSH) have often been measured [131,132,133,134,135,136,137,138,139,140,155,157,162,202]. Alternatively, oxidation of polyunsaturated fatty acids is also measured to evaluate oxidative stress in diabetic animals.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
See 2 more Smart Citations